Dermatoanthropology of Ethnic Skin and Hair - Vashi, Neelam A.; Maibach, Howard I.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
Dermatoanthropology of Ethnic Skin and Hair is a comprehensive text that extensively examines cutaneous disease in persons with skin of color. The breadth of knowledge in this book encompasses the wide scope of dermatologic disease with 26 distinct and unique chapters. It serves as a guide to the diagnosis and treatment of skin disorders for those populations with darker skin types. Vashi and Maibach$1 (Bs Dermatoanthropology of Ethnic Skin and Hair provides an overview of medical, surgical, and cosmetic dermatology in addition to providing an extensive anthropological and basic science background to fully understand skin disorders in persons of color. Topics of discussion include anthropology of skin and hair, biophysical properties of ethnic skin, structure and function of the skin, physiologic pigmentation, mucosal lesions, acne, rosacea, inflammatory disorders, infections, autoimmune disorders, connective tissue disease, hyperpigmentation, hypopigmentation and depigmentation, keloids, scarring, pediatric disease, alopecias, adnexal disorders, common cosmetic concerns and treatments, and cultural considerations.s
1. The Anthropology of Skin Colors: An Examination of the Evolution of Skin Pigmentation and the Concepts of Race and Skin of Color -- 2. The Impact of Skin and Hair Disease in Ethnic Skin -- 3. Biophysical Properties of Ethnic Skin -- 4. Differences in Skin Structure and Function in Ethnic Populations -- 5. Photosensitivity and Photoreactivity in Ethnic Skin -- 6. Stratum Corneum Lipids and Water-Holding Capacity -- 7. Physiologic Pigmentation -- 8. Mucosal Lesions in Skin of Color -- 9. Acne and Rosacea -- 10. Inflammatory Disorders -- 11. Tinea Versicolor and Tinea Capitis -- 12. Autoimmune and Connective Tissue Disease in Skin of Color -- 13. Disorders of Hyperpigmentation -- 14. Disorders of Hypopigmentation and Depigmentation -- 15. Keloids and Hypertrophic Scarring -- 16. Skin Cancer -- 17. Pediatric Dermatology -- 18. The Anthropology of Human Scalp Hair -- 19. Alopecias and Disorders of the Hair Follicle -- 20. Adnexal Disorders -- 21. Skin Aging in Individuals with Skin of Color -- 22. Common Cosmetic Concerns and Approaches -- 23. Treatment Strategies for Hyperpigmentation -- 24. Chemical Peels in Ethnic Skin -- 25. Laser Treatment in Ethnic Skin -- 26. Cultural Considerations.
Keywords: Medicine; Dermatology; Medicine & Public Health; Dermatology